A novel treatment option for Kummell’s disease using percutaneous kyphoplasty with a mesh-hold bone filling container - Bingyan Mao; Wencong Wang; Qiang Wang; Lei Li (Scientific Reports)
Abstract Percutaneous kyphoplasty (PKP) is an effective, minimally invasive treatment for Kummell’s disease, but challenges like cement leakage, fracture, and displacement remain. This study explores the use of PKP with a mesh-hold bone filling container for this disease.A retrospective analysis was conducted on nine Kummell’s disease cases treated with this technique at a spinal surgery department from June 2016 to May 2022. Pre- and postoperative evaluations included X-rays, CT scans, and 3D reconstructions. Parameters like vertebral heights, kyphotic angle, operation time, blood loss, and bone cement issues were measured. Efficacy was assessed using ODI and VAS scores.Statistical analysis showed no significant difference in posterior vertebral height before and after treatment. All other indexes improved significantly postoperatively and at follow-up. No cement leakage or displacement occurred.PKP with a mesh-hold bone filling container is a promising treatment for Kummell’s disease. It enhances reduction quality, ensures adequate bone cement filling, and reduces issues related to cement leakage, fracture, and displacement.